Pengembangan Media Edukasi Parenting Berbasis Website Menggunakan Motion Graphic dan Material Design Guidelines bagi Keluarga Muda - Mulyadi Mulyadi; Merty Megawati; Suryawahyuni Latief; Ahmad Husna Ahadii; Ahmad Louis; Faiza Rini (CV. Creative Tugu Pena, 2026)
The rapid development of digital technology requires young families to possess adaptive parenting knowledge that aligns with children's developmental needs in the digital era. However, limited access to interactive and user-friendly parenting education media remains a challenge for many young parents. This study aimed to develop a website-based parenting education media using motion graphics and material design guidelines to improve young families’ understanding of child parenting. The study employed a Research and Development (R&D) method using the 4D model combined with the Multimedia Development Life Cycle (MDLC). The research stages included define, design, development, and disseminate, along with multimedia processes consisting of concept, design, material collection, assembly, testing, and distribution. The research subjects involved 33 young parents in Simpang Rimbo Village, Jambi City, selected through purposive sampling. Data were collected through observation, interviews, documentation, questionnaires, pre-tests, and post-tests. Data analysis was conducted using normality, homogeneity, and Wilcoxon Signed Rank tests with SPSS version 27. The results indicated that the EduParent media achieved a “very good” category based on media expert validation (83.7%) and material expert validation (97.5%). User testing also demonstrated high satisfaction levels regarding interface design, usability, and material relevance. Furthermore, the Wilcoxon test showed a significance value of 0.001 (<0.05), indicating a significant improvement in parenting understanding after using the application. This study contributes to the development of interactive and responsive website-based digital parenting education media tailored to the characteristics of young families in the digital era.